Penguatan Sistem Manajemen Sosial Pesantren dalam Mewujudkan Lingkungan Anti-Bullying Melalui Pendekatan Ukhuwah Diniyah Islamiyah - Hisbidaturrosidah, Hisbidaturrosidah; Apriza, Lisna; Cahyani, Safira; Vebriana, Alvina Putri; Kurnia, Agus (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Bullying is a form of violence that often occurs among students, including in Islamic boarding schools, and has serious impacts such as trauma and death, thus threatening the quality of education. This community service activity aims to increase students' awareness of the importance of solidarity and Islamic brotherhood as an effort to prevent bullying behavior at the Madrasatul Quraniyah Islamic Boarding School, West Lombok. Islamic boarding schools have a strategic role in shaping character and strengthening the values of brotherhood. The method used is service-learning through material delivery, discussion, questions and answers, and evaluation through pre-tests and post-tests. The results showed a significant increase in students' understanding of bullying and Islamic brotherhood, as evidenced by the dominance of "Agree" and "Strongly Agree" answers in the post-test. This brotherhood-based approach has proven effective in preventing bullying and strengthening solidarity in Islamic boarding schools, as well as supporting the achievement of SDGs point 4 (Quality Education) and point 16 (Peace and Justice).